Voices of Protest: A Study of Manohar Malgonkar’s Fictional Women - Dr Seema Miglani (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2024)
Contemporary fiction aims at bringing the marginalized into the mainstream so as to accord voice to the powerless, the oppressed and the dispossessed. The writers especially the women writers in India seem to grapple with the multifarious aspects and concerns of contemporary women in their writings. They emphatically present detailed accounts of women’s lives, experiences, emotions, ideas and pre-occupations. They present women in love, women in adjustment, women in emotional conflict, women in whirlpool of difficulty and ultimately women desiring empowerment to move confidently in the new world as ‘a new woman’. However, Manohar Malgonkar has often been considered a male chauvinist writer and it is alleged that his male characters are superior to his women, who are either objects of entertainment, playing subservient role or social rebels. This paper tries to exonerate him of this reductionist view and highlight the aspects, which reveal his sympathy for the woman cause, his adoration for strong and modern women capable of taking challenges at the face, and surviving, that too with confidence.